Flavone Enhances Dengue Virus Type-2 (NGC Strain) infectivity and replication in vero cells - Zandi, K.; Lani, R.; Wong, P. F.; Teoh, B. -T.; Sam, S. -S.; Johari, J.; Mustafa, Mohd Rais; AbuBakar, Sazaly (MDPI, 2012)
This study investigates the effects of 2-phenyl-1-benzopyran-4-one (flavone) on DENV-2 infectivity in Vero cells. Virus adsorption and attachment and intracellular virus replication were investigated using a foci forming unit assay (FFUA) and quantitative RT-PCR, respectively. Addition of flavone (100 μg/mL) significantly increased the number of DENV-2 foci by 35.66 ± 1.52 and 49.66 ± 2.51 when added during and after virus adsorption to the Vero cells, respectively. The average foci size after 4 days of infection increased by 33 ± 2.11 and 89 ± 2.13. The DENV-2 specific RNA copy number in the flavone-treated infected cells increased by 6.41- and 23.1-fold when compared to the mock-treated infected cells. Flavone (100 μg/mL) did not promote or inhibit Vero cell proliferation. The CC50 value of flavone against Vero cells was 446 µg/mL. These results suggest that flavone might enhance dengue virus replication by acting antagonistically towards flavonoids known to inhibit dengue virus replication.